2014
DOI: 10.1088/0953-4075/47/13/135401
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of laser-produced carbon nanoparticle plasmas and high-order harmonic generation of ultrashort pulses in clustered media

Abstract: We analyse the morphology of the laser plasmas produced on surfaces containing various carbon clusters (nanotubes, nanofibres, fullerenes, and nanoparticles). It is shown that the presence of C5–C25 nanoparticles in the laser plasmas coincides with the enhancement of harmonics in the spectral range of 40–80 nm. We suggest that these nanoparticles, rather than larger clusters, play a decisive role in the observed growth of harmonic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The moderate fluencies of nanosecond pulses also increased the lifetime of the targets and provided better survival of the original nanostructures being ablated and spread in the plasma plume without their destruction. It was demonstrated that, in the case of laser ablation of C 60 , MW CNT, CNF, and DN [25] at the experimental conditions similar to ours, the transmission electron microscopy analysis of deposited debris has shown that laser-produced plumes contained the original nanostructures.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The moderate fluencies of nanosecond pulses also increased the lifetime of the targets and provided better survival of the original nanostructures being ablated and spread in the plasma plume without their destruction. It was demonstrated that, in the case of laser ablation of C 60 , MW CNT, CNF, and DN [25] at the experimental conditions similar to ours, the transmission electron microscopy analysis of deposited debris has shown that laser-produced plumes contained the original nanostructures.…”
Section: Resultssupporting
confidence: 73%
“…Earlier reported TOFMS spectra have demonstrated the similarities between the MW CNT and CNF, with the presence of small carbon C n fragments (with n varied up to 20) and no ions higher than low-sized carbon clusters in the mass spectra up to 5000 mass/charge units [25]. Additionally, the emission from ablated MW CNT and C 60 targets showed almost similar spectra (Figure 2), with strong relative lines for CIII and CIV transitions.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations